Online intercultural education and study abroad theory into practice - Jackson, Jane 1954- (Internationalization in higher education, 2019)
With the increasing focus on international education and study abroad programmes, Online Intercultural Education and Study Abroad meets the need for a text that addresses ways in which technology may be harnessed to enhance student experience. Combining case studies with theoretical insights, this book critically investigates the effectiveness of a fully online study abroad intervention that was designed to optimise intercultural learning in an international context. Intercultural education researchers and practitioners are provided with theory-based practical ideas such as eLearning strategies and online mentoring tips to help students maximise their intercultural education journey, intercultural competence development, and social engagement while abroad. Both practical and research-focused, this volume considers a wide range of topics, including: Contemporary notions of experiential learning Guided critical reflection through e-mentoring A social contructivist orientation towards eLearning pedgagogy Tools to help understand and measure learner development abroad Online Intercultural Education and Study Abroad is suitable for both novice and experienced study abroad practitioners, researchers, and administrators. Satisfying the growing interest in using eLearning within study abroad programmes, this book will be a necessary point of reference for any institution that aims to enhance international educational experience, especially through the use of technology